Development and implementation of “environmental game” as tool for environmental education - Silva, Natacha; Mineo, Marina Farcic (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Environmental education and the professor are disconnected of simple transmission of content about nature, promoting the ongoing process of building students knowledge. The educational games have been used in order to improve this process. This study developed na educational game called "Environmental Game", a memory game adaptation and verified if would be an effective strategy on Environmental Education. The game was formed by the union of a tip card and other with a corresponding figure in the categories: ecology, biomes, natural resources and endangered animals. The test was applied to a class of Technical Course in Environment in São Joaquim da Barra, São Paulo state. During the activity, each pair of cards chosen was discussed between students and professor regarding their importance to environment and, ultimately, answered a questionnaire about this tool. Overall, they evaluated the game how entertaining, a good exercise for memory and content reviewer. Then the “Environmental Game" was an appropriate strategy for promoting sustainability content related and an effective tool in environmental education learning, providing debate and the contextualized knowledge construction.